(untitled) - Meyers, Robin R. (San Francisco, 2006)
Having "spent [his] whole life trying to persuade people that 'liberal' is not a dirty word, and that Christianity is a way of life, not a set of creeds and doctrine demanding total agreement," Meyers, a United Church of Christ minister and Oklahoma City University professor of rhetoric, became an Internet celebrity when his November 2004 antiwar remarks bounced from continent to continent. In response, Meyers expanded 10 of his most salient points into a self-titled manifesto which not only highlights the dichotomy between the right's talk of Christian values and its walk.
Keywords: Fundamentalism,Conservatism,Conservatism; Religious aspects,Christianity; United States,United States